On a Possible Interaction Between ADP and Mechanical Stimulation in Platelet Activation - Aursnes, Ivar; Vikholm, Vibeke (Thrombosis and Haemostasis, 1984)
Freshly drawn blood with inhibited plasma coagulation, but normal Ca++-concentration, was lightly centrifuged to produce platelet rich plasma (PRP). In order to minimize mixing of the various parts of the blood during the centrifugation, the red cells were centrifuged into a “cushion” of albumin in the bottom of the tube. Platelets harvested from the different parts of the centrifuge tube exhibited different degrees of activation, i. e. they possessed different abilities to aggregate when tested afterwards in an aggregometer. Complete ADP scavenging during the centrifugation inhibited the platelet activation, and it was therefore assumed that ADP released from red cells during the centrifugation was partly responsible for this. But as the ADP concentration at hand could be significantly reduced enzymatically without reducing the activation of the platelets by the centrifuge, mechanical stimulation during the centrifugation was postulated as a contributing factor. Prostaglandin synthesis inhibition during the centrifugation retarded the activation of the platelets in the tube.
Keywords: ADP; Platelet aggregation; ASA